2021
DOI: 10.5946/ce.2021.157
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Linked Color Imaging and Blue Laser/Light Imaging in the Screening, Diagnosis, and Treatment of Superficial Colorectal Tumors

Abstract: Considering its contribution to reducing colorectal cancer morbidity and mortality, the most important task of colonoscopy is to find all existing polyps. Moreover, the accurate detection of existing polyps determines the risk of colorectal cancer morbidity and is an important factor in deciding the appropriate surveillance program for patients. Image-enhanced endoscopy is an easy-touse modality with improved lesion detection. Linked color imaging (LCI) and blue laser/light imaging (BLI) are useful modalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Image-enhanced endoscopy has recently been developed to improve the ADR in daily practice, and linked color imaging (LCI) has attracted particular attention (Figure 1). The LASEREO laser endoscope (Fujifilm, Tokyo, Japan) combines two short-wavelength laser beams (410 nm and 450 nm) and a phosphor excited by a 450-nm laser output to enable white light, blue laser imaging, and LCI observations [6]. Recent studies have indicated that using LCI increases background blood vessel visibility and enhances reddish hues; therefore, redness associated with inflammation, polyps, and cancer is enhanced, improving the ADR [7,8].…”
Section: Tablesmentioning
confidence: 99%
“…Image-enhanced endoscopy has recently been developed to improve the ADR in daily practice, and linked color imaging (LCI) has attracted particular attention (Figure 1). The LASEREO laser endoscope (Fujifilm, Tokyo, Japan) combines two short-wavelength laser beams (410 nm and 450 nm) and a phosphor excited by a 450-nm laser output to enable white light, blue laser imaging, and LCI observations [6]. Recent studies have indicated that using LCI increases background blood vessel visibility and enhances reddish hues; therefore, redness associated with inflammation, polyps, and cancer is enhanced, improving the ADR [7,8].…”
Section: Tablesmentioning
confidence: 99%
“…It can project several images such as WLI, BLI, LCI, and BLI-bright (BLI-brt). 1 , 2 In WLI, blue, green, and red lights are combined to create a clear image. High contrast is maintained using blue-violet light (short wavelength, 410 nm).…”
Section: Principles Of Fujifilm Ieementioning
confidence: 99%
“…7,8 Many studies have shown the efficacy of lesion visibility and polyp detection under LCI observation. [9][10][11][12][13][14][15] On the other hand, an endoscope with a light-emitting diode (LED) light source (ELUXEO; Fujifilm) has been marketed since 2017 in the West and since 2020 in Japan. 16,17 Multilight technology from four-color LED lights (blue-violet, blue, green, and red) provides BLI and LCI.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, linked color imaging (LCI) was developed and LCI has a brighter view and yellowish residual liquid in poor preparation, making neoplastic lesions and inflammatory areas reddish 7,8 . Many studies have shown the efficacy of lesion visibility and polyp detection under LCI observation 9–15 …”
Section: Introductionmentioning
confidence: 99%